2021
DOI: 10.1016/j.jece.2021.106843
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of activated carbon from the residues of the mushroom (Agaricus bisporus) production chain for the adsorption of the 2,4-dichlorophenoxyacetic herbicide

Abstract: The production of the edible mushroom Agaricus bisporus occurs on a world scale, where tons are constantly produced. At the same time, this production generates a large amount of waste that needs to be adequately conditioned. Therefore, mushroom residues were used to develop activated carbon for the removal of 2,4-D-the developed adsorbent showed a microporous structure with several spaces on the surface. The FTIR analysis showed that the activated carbon has functional groups such as aromatic rings, carboxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 83 publications
5
18
0
3
Order By: Relevance
“…This effect is related to increasing the atrazine concentration gradient, which leads to higher intraparticle mass transfer and external mass transfer rates [65]. This behavior was also reported by Lazarotto et al [13] and Franco et al [65] when using activated carbons to remove 2,4-dichlorophenoxyacetic and phenol, respectively.…”
Section: Kinetics and Application Of The Ldf Modelsupporting
confidence: 69%
See 2 more Smart Citations
“…This effect is related to increasing the atrazine concentration gradient, which leads to higher intraparticle mass transfer and external mass transfer rates [65]. This behavior was also reported by Lazarotto et al [13] and Franco et al [65] when using activated carbons to remove 2,4-dichlorophenoxyacetic and phenol, respectively.…”
Section: Kinetics and Application Of The Ldf Modelsupporting
confidence: 69%
“…Thus, it is confirmed that BCC has potential atrazine removal in real water samples. In the study by Lazarotto et al [13], the authors contaminated a water sample from the Jacuí River (Agudo, Rio Grande do Sul, Brazil) with 10 mg L -1 of the 2,4-D herbicide. They verified the removal of 70% using activated charcoal.…”
Section: River Water Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies confirmed that pyrolysis followed by chemical activation with ZnCl 2 causes morphological changes in materials of plant origin, such as eucalyptus residues (Han et al 2020), olive pits (Baldoni et al 2020), leaves of folium cycas (Kong et al 2020), peanut husks (Georgin et al 2016), seed pods of Jacaranda mimosifolia (Georgin et al 2021), fruit residues from the Ceiba sp. forest species (Franco et al 2021), Diospyros kaki fruit residues (Salomón et al 2022), residues from the mushroom Agaricus bisporus (Lazarotto et al 2021) and residual peel of pitaya fruit (Georgin et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Yapılan bazı çalışmalarda yüzey alanı ve verim açısından KOH ile aktifleştirme, çeşitli uygulamalarda sodyum hidroksitten daha iyi sonuçlar verdiği tespit edilmiştir (Heidarinejad, 2020) Kültür mantarı yetiştiriciliğinde popüler olan beyaz şapkalı mantarın dünya genelinde sürekli artan miktarda üretimi söz konusudur. Bu üretim, beraberinde büyük miktarda misel ve sap gibi atıkları da meydana getirmektedir (Lazarotto et al, 2021). Bu atıkların AC gibi faydalı bir ürüne dönüştürülmesi ülke ve dünya ekonomisi açısından oldukça değerlidir.…”
Section: Introductionunclassified